The stepsister's tale - Barrett, Tracy, 1955- (Harlequin Teen, 2014)
Jane cares for her mother and sister until her stepfather dies, leaving nothing but debts and Jane's spoiled stepsister behind, but a mysterious boy from the woods and an invitation to a royal ball are certain to change her fate.